Significance loss brings to extreme self-care related behaviors: the role of interpersonal influence and obsessive (vs. harmonious) passion - Contu, Federico; Pierro, Antonio (Frontiers in Psychology, 2024)
Building on Significance Quest Theory (Kruglanski et al., 2022), we hypothesized that significance loss feelings can bring people to extreme self-care related behaviors via a) the susceptibility to interpersonal influence, and b) the development of a predominance of obsessive (vs. harmonious) passion towards the self-care. To test these hypotheses, we ran one cross-sectional study among voluntary participants (N=401). Results confirmed our hypotheses, suggesting that physical appearance is perceived as a fruitful and useful route to maintain or even restoring ones' personal sense of significance. Notably, these results shed light on another scope that can be exploited to achieve social significance (i.e., physical appearance) through extremism, and could represent a starting point to design practical intervention to reduce the examined extreme behaviors.